Probe into the Origin of Personal Pronoun “朕” (zhèn) - Jinjing, Xu (Sinología hispánica. China Studies Review, 2018)
In Chinese, "朕" (zhèn) is a very special personal pronoun. Since the First Emperor of Qín, in the long history of two thousand years in China, it has always existed as the privilege pronoun of the emperor. So, why two thousand years ago, before the emperor to set the word, but not other words? The word "朕" has any special meaning and role? This article attempts to analyze the use of the Chinese characters in Oracle and concludes the results of the reconstructions of Old Chinese in recent years. This article attempts to analyze the use of the Chinese characters in Oracle and concludes the results of the reconstructions of Old Chinese in recent years. It is preliminarily thought that the character "朕" represented by the Chinese characters are not just the forms of first-person pronouns, but two: one for the first-person pronouns are qualified, the other for the first-person pronouns contrastive form. At the same time, we try to propose two suffixes */ɯ/ and */m/.